Workers and Jobs: The Balance is Shifting - O’Hara, Frank (Maine Policy Review, 1998)
In an era when the availability of skilled labor is deemed one of the most important ingredients of economic growth, Maine faces a labor shortage that is unlikely to disappear soon. Frank O’Hara traces the rapid growth of Maine’s labor force through the 1970s and 1980s, its slow growth through the 1990s, and explains why slow to no growth can be expected in the future. Unlike a decade ago when concern over the availability of Maine workers disappeared with the onset of a recession, O’Hara predicts this labor shortage is here to stay and has implications for al regions of the state. He describes several scenarios that could result from this labor shortage, including the end of economic growth, the stimulation of a new period of in-migration, and/or an improvement in workers’ conditions that is driven by the needs of business to retain its most talented workers.